Addition of EM4 Probiotics in Commercial Feed For The Growth of Milkfish Juvenils (Chanos chanos) - Sri Sukari Agustina; Ahmad Muslim Laika; Erwin Wuniarto (Universitas Islam Lamongan, 2025)
Milkfish production can be increased in aquaculture if feeding and the use of artificial high protein feed can be optimized. Optimal feeding can be done by adding probiotics to the feed, one of which is by using EM4. This study aims to compare the concentration of the addition of probiotic EM4 in commercial feed so that optimal growth of juvenile milkfish (Chanos chanos) is obtained. This research was conducted in the community ponds of Toiba Village, Bualemo District, Banggai Regency from May to July 2022. This research uses an experimental method which is carried out in one pond plot. There were nine fixed cages with a width of 30 cm and a height of 30 cm used for maintenance. The experimental design used in this study was a completely randomized design (CRD) with 3 treatments and 3 replications. Parameters observed in this study were Specific Growth Rate (SGR), Feed Conversion Ratio (FCR), Survival (SR) and water quality. The results of the research showed that treatment B provided the best Specific Growth Rate and Feed Conversion Ratio for juvenile milkfish because the difference in the number of bacteria contained in EM4 probiotics can affect the absorption of fish nutrients because the more bacterial population in the digestive tract will increase the availability of nutrients that are ready to be absorbed in the digestive tract. This increase in digestibility is the same as the higher nutrients available to be absorbed by the body which will affect growth and Feed Conversion Ratio.